Exposure to a glyphosate-based herbicide during pregnancy and lactation induces neurobehavioral alterations in rat offspring - Gallegos, Cristina Eugenia (2016)
The impact of sub-lethal doses of herbicides on human health and the environment is a matter of controversy. Due to the fact that evidence particularly of the effects of glyphosate on the central nervous system of rat offspring by in utero exposure is scarce, the purpose of the present study was to assess the neurobehavioral effects of chronic exposure to a glyphosate-containing herbicide during pregnancy and lactation. To this end, pregnant Wistar rats were exposed through drinking water to 0.2% or 0.4% of a commercial formulation of glyphosate (corresponding to a concentration of 0.65 or 1.30 g/L of glyphosate, respectively) during pregnancy and lactation and neurobehavioral alterations in offspring were analyzed. The postnatal day on which each pup acquired neonatal reflexes (righting, cliff aversion and negative geotaxis) and that on which eyes and auditory canals were fully opened were recorded for the assessment of sensorimotor development. Locomotor activity and anxiety levels were monitored via open field test and plus maze test, respectively, in 45- and 90-day-old offspring. Pups exposed to a glyphosate-based herbicide showed early onset of cliff aversion reflex and early auditory canal opening. A decrease in locomotor activity and in anxiety levels was also observed in the groups exposed to a glyphosate-containing herbicide. Findings from the present study reveal that early exposure to a glyphosate-based herbicide affects the central nervous system in rat offspring probably by altering mechanisms or neurotransmitter systems that regulate locomotor activity and anxiety.